Harmful Algal Bloom in Kuantan Port, Pahang Malaysia: the presence of Paralytic Shellfish Poisoning (PSP) species, Pyrodinium Bahamense var Compressum and Alexandrium Tamiyavanichii - Mohammad Noor, Normawaty; Mohammad Bunnori, Noraslinda; Hamdan, Nurul Ashima; Lim, Po Teen; Leaw, Chui Pin; Md Noor, Azlan; Kemat, Norazizah (2015)
Harmful Algal Bloom (HAB) is a proliferation of algae which naturally produce biotoxins and may harm the health of human, the environment and the organisms associated with it. The first HAB case has been reported in Kuantan Port on November 2013, and followed by the second episode on August 2014. The toxicity level reported during the second case was as high as 3500 µg STX/100 g. Ten persons were hospitalized, showing the symptoms of paralytic shellfish poisoning (PSP) after consumed the contaminated shellfish. Therefore, this study was conducted at Kuantan Port to identify the causative organisms responsible for these events. Water samples were collected monthly for a period of six months from August 2014. HAB species were identified based on their outer morphology using light and epifluorescence microscopy, and supported by the molecular evidence based on the LSU rDNA and ITS makers. The density of cells were determined using Sedgwick rafter counting chamber under a light microscope at a magnification of 100×. Our results revealed the occurrence of several HAB species including two PST-producing species, viz. Pyrodinium bahamense var. compressum and Alexandrium tamiyavanichii. The highest cell density of P. bahamense and A. tamiyavanichii were 6 × 104 cells/L and 1.5 × 105 cells/L, respectively. This study reported, for the first time, the occurrence of P. bahamense and A. tamiyavanichii in Pahang coast, east Peninsular Malaysia, and confirmed that the PSP events in Kuantan Port were attributed to the species. The presence of these species further indicates that several safety measures need to be considered to safeguard public health, particularly in Pahang coastal waters.